HIF-1α inhibition by diethylstilbestrol and its polyacetal conjugate in hypoxic prostate tumour cells: insights from NMR metabolomics. (26th November 2017) - Armiñán, Ana; Mendes, Luís; Carrola, Joana; Movellan, Julie; Vicent, María J.; Duarte, Iola F.
Abstract: In this study, we have employed 1 H NMR metabolomics to assess the metabolic responses of PC3 prostate tumour cells to hypoxia and to pharmacological HIF-1α inhibition by DES or its polyacetal conjugate tert -DES. Oxygen deprivation prompted a number of changes in intracellular composition and metabolic activity, mainly reflecting upregulated glycolysis, amino acid catabolism and other compensatory mechanisms used by hypoxic cells to deal with oxidative imbalance and energy deficit. Cell treatment with a non-cytotoxic concentration of DES, under hypoxia, triggered significant changes in 17 metabolites. Among these, lactate, phosphocreatine and reduced glutathione, whose levels showed opposite variations in hypoxic and drug-treated cells, emerged as possible markers of DES-induced HIF-1α inhibition. Furthermore, the free drug had a much higher impact on the cellular metabolome than tert -DES, particularly concerning polyamine and pyrimidine biosynthetic pathways, known to be tightly involved in cell proliferation and growth. This is likely due to the different cell pharmacokinetics observed between free and conjugated DES. Overall, this study has revealed a number of unanticipated metabolic changes that inform on DES and tert -DES direct cellular effects, providing further insight into their mode of action at the biochemical level.